A Novel Peptide Thrombopoietin Mimetic Designing and Optimization Using Computational Approach - Singh, Vimal Kishor; Kumar, Neeraj; Kalsan, Manisha; Saini, Abhishek; Chandra, Ramesh (Frontiers in Bioengineering and Biotechnology, 2016)
Thrombopoietin receptor (TPOR) is a cytokine receptor protein; activation of cell surface TPOR by thrombopoietin (TPO) triggers an intracellular cascade of megakaryocytopoiesis for the formation of platelets. TPO is a glycoprotein hormone which stimulates megakaryocytes formation and maturation to platelets in bone marrow. Ex vivo megakaryocytopoiesis is in highlight for its vast role in therapeutics and field of regenerative medicine. For therapeutic uses, various TPO alternatives have been used however they are associated with issues like recombinant TPO administration is associated with the generation of auto antibodies and its production is an expensive process. Moreover, reported thrombopoietin mimetic peptide (TMP) has no sequence homology with TPO and low specificity to TPOR. Hence, in this study, a novel peptidic TPO mimetic is designed through computational studies by studying the binding sites of TPO and TMP to TPOR and analogs of known mimetics. Screening of combinatorial library was done through molecular docking using ClusPro and mimetic-9 was found to have better binding score of -938.8 kcal/mol with seven hydrogen bonds and a high number of hydrophobic interactions, than known mimetic TMP with docking score of -798.4 kcal/mol and TMP dimer with docking score of -811.9 kcal/mol for TPOR. Mimetic-9 interaction with TPOR was further assessed by the molecular dynamics simulation and their complex was found to be stable with an RMSD value of 0.091 Aº. Resulting mimetic-9 was found to have overall good physiochemical properties with positive grand average hydropathy (GRAVY) score and high instability index score and it was found to be localized in the extracellular region. The designed mimetic-9 might prove to be a useful lead molecule for mimicking the role of TPO and to help for platelet production in vitro with higher efficiency.